On the topology of Sasakian manifolds - Pitiş, Gheorghe (MATHEMATICA SCANDINAVICA, 2003)
The notion of q-bisectional curvature of a Sasakian manifold M is defined. It is proved that if M has lower bounded q-bisectional curvature and contains a compact invariant submanifold tangent to the structure vector field then M is compact. Myers and Frankel type theorems for Sasakian manifolds with lower bounded and positive q-bisectional curvature, respectively, are also given.